PENENTUAN TOTAL MIKROBA INDIKATOR, NITRAT, DAN FOSFAT PADA SUNGAI TAPUNG KIRI - Rosidah '; Yuli Haryani; Ganis Fia Kartika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The aim of this study was to analyze physicochemical parameters and total microbial indicators of river water in Tapung Kiri river. Water samples were taken from 4 sampling sites in July 2013. The results showed that the range of TDS, turbidity, electrical conductivity, and nitrate in the water samples were 9-21 mg/L, 3.89-41.1 NTU, 17.72-42.0 µs/cm, and 0.112-0.508 mg/L, respectively which were below of the threshold value. Temperature, pH, DO, and phosphate content range were 27-29oC, 4.75-6.30, 3.36-3.96 mg/L, and 0.089-0.235 mg/L at the threshold value based on PP No 82 2001. The level of Coliform and E. coli contamination in the water samples were 0.4-18×10 3 CFU/mL and 0.1-4×10 3 CFU/mL. The level of total bacteria contamination was found in all samples ranged from 0.43-4.6×10 4 MPN/mL, while the fungi contamination was 0.1-0.3×10 3 CFU/mL.